Optimal timing and treatment strategy for pancreatic cancer - Gamboa, Adriana C. (J Surg Oncol, 2020)
BACKGROUND: For pancreatic adenocarcinoma (PDAC), no studies have established any association between earlier treatment initiation and long-term outcomes. In addition, an optimal type of initial treatment for the localized disease remains ill-defined. METHODS: Patients in the National Cancer Database (2004-2015) with clinical stage I (CS-I) and II (CS-II) PDAC who underwent curative-intent resection were included. Optimal time from diagnosis-to-treatment including neoadjuvant chemotherapy, neoadjuvant chemoradiation, or upfront surgery was assessed. An optimal type of treatment was evaluated. The primary outcome was overall survival (OS). RESULTS: Among 29 167 patients, starting any treatment within 0 to 6 weeks was associated with improved median OS compared with 7 to 12 weeks (21.0 vs 20.1 months; P = .004). This persisted when accounting for sex, race, and Charlson-Deyo score (hazard ratio [HR], 0.94; P = 0.02) and on subset analysis for CS-I (23.5 vs 21.8 months; P = .04) and CS-II (19.4 vs 18.3 months; P = .03). Neoadjuvant chemotherapy was associated with improved OS compared with neoadjuvant chemoradiation (25.6 vs 22.7 months; P <.0001) or US (25.6 vs 20.1 months; P <.0001) even when accounting for sex, race, and Charlson-Deyo score (neoadjuvant chemoradiation: HR, 0.86; P < .001; US: HR, 0.79; P < .001). This improvement persisted in subset analysis with NC compared with neoadjuvant chemoradiation (CS-I: 28.6 vs 25.0 months; CS-II: 25.0 vs 22.9 months; both P < .0001) and to US (CS-I: 28.6 vs 22.9 months; CS-II: 24.7 vs 18.4 months; both P < .0001). On multivariable analysis for each CS-I/CS-II, NC remained associated with 20% improved survival compared with neoadjuvant chemoradiation or upfront surgery. CONCLUSIONS: For PDAC, initiation of therapy within 6 weeks from diagnosis is associated with improved survival, with neoadjuvant chemotherapy associated with the best survival compared with neoadjuvant chemoradiation or upfront surgery.